An autopsy case of nearly complete ossification of the stylohyoid chain: Eagle syndrome in forensic aspect. (May 2018) - Kato, Hideaki; Kanno, Sanae; Ohtaki, Jun; Nakamura, Yoshimi; Kobayashi, Katsumasa; Aoki, Yasuhiro
Highlights: Eagle syndrome is caused by a long styloid process or styloid chain ossification. Eagle syndrome is a rare disorder. Symptoms vary greatly, from cervicofacial pain to life-threatening cerebral ischemia. A case of drowned 77-year-old man with ossified stylohyoid chain is presented. Significance of Eagle syndrome in forensic casework is discussed.